How Should Pensions be Taxed? Theoretical Considerations and the Scandinavian Experience - Torben M. Andersen (Center for Economic Studies and ifo Institute (CESifo), 2015)
How should pensions be taxed? In many cases pension savings are usually taxed more leniently than other forms of savings. What is the rationale for this? And are those concerns best targeted via taxation or mandatory pension savings? These issues are discussed with outset in the experience of the Scandinavian countries (Denmark and Sweden). These countries are also interesting because they have implemented a dual income taxation scheme; i.e. they pursue an ETT-taxation regime vis a vis pensions. It is argued that the incentive structure related to pension savings and retirement can not be seen independently from how private pensions (and savings more generally) affect public pensions via meanstesting. The effective rates of taxation may thus differ significantly from the nominal rates. For Denmark and Sweden it is shown that the effective tax rates on pension savings can be rather high, and for low/medium income close to 100%.
Keywords: H20; 330; pensions; taxation; means-testing; distribution; effective tax rates